Membangun Budaya Kerja yang Positif melalui Manajemen yang Efisien - Alvareta, Bagas (Jujurnal Publisher, 2024)
This study explores the significant role of efficient management practices in fostering a positive work culture within organizations. By focusing on transformational leadership, effective communication, employee engagement, and human resource management, the research demonstrates how these factors contribute to a healthier, more productive work environment. The study draws upon existing theories, including Bass & Avolio’s transformational leadership model and Saks’ employee engagement theory, to investigate how leadership styles and employee involvement impact organizational culture. Through a thorough literature review, the research identifies key practices that support the development of a positive work culture, including empowerment, recognition, and clear communication channels. The findings suggest that organizations implementing efficient management practices not only enhance employee satisfaction and loyalty but also improve overall organizational performance. This research highlights the importance of strategic management in building a strong and sustainable organizational culture that drives long-term success.